1999
DOI: 10.1073/pnas.96.9.4959
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cytoplasmic irradiation with alpha particles induces mutations in mammalian cells

Abstract: Ever since x-rays were shown to induce mutation in Drosophila more than 70 years ago, prevailing dogma considered the genotoxic effects of ionizing radiation, such as mutations and carcinogenesis, as being due mostly to direct damage to the nucleus. Although there was indication that alpha particle traversal through cellular cytoplasm was innocuous, the full impact remained unknown. The availability of the microbeam at the Radiological Research Accelerator Facility of Columbia University made it possible to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
274
3
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(293 citation statements)
references
References 31 publications
13
274
3
3
Order By: Relevance
“…They proposed that the de novo production of new aberrations in the descendants of irradiated cells was due to oxidative damage but had no explanation for why the oxygen radical generation was persistently elevated. Recent data from several laboratories Lorimore et al, 1998;Azzam et al, 1999;Wu et al, 1999) have shown that all the endpoints which characterize 'genomic instability', can in fact be induced in cells that were never directly exposed to irradiation. Wu et al (1999) and Azzam et al (1999) showed mutations in cells that were not traversed by a radiation track.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They proposed that the de novo production of new aberrations in the descendants of irradiated cells was due to oxidative damage but had no explanation for why the oxygen radical generation was persistently elevated. Recent data from several laboratories Lorimore et al, 1998;Azzam et al, 1999;Wu et al, 1999) have shown that all the endpoints which characterize 'genomic instability', can in fact be induced in cells that were never directly exposed to irradiation. Wu et al (1999) and Azzam et al (1999) showed mutations in cells that were not traversed by a radiation track.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from several laboratories Lorimore et al, 1998;Azzam et al, 1999;Wu et al, 1999) have shown that all the endpoints which characterize 'genomic instability', can in fact be induced in cells that were never directly exposed to irradiation. Wu et al (1999) and Azzam et al (1999) showed mutations in cells that were not traversed by a radiation track. Lorimore et al (1998) showed that persistent chromosomal aberrations following alpha particle irradiation were found in the parts of the culture which were not ever hit by a particle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a damage response may initiate as yet undefined pathways that ultimately lead to the generation of a BSE in non-irradiated cells, and hints at a tissue-level response to radiation injury moderated by some of the same proteins that orchestrate the intracellular response to DNA damage. Although an intracellular IR-induced signaling response has been demonstrated (Wu et al, 1999), it has also been shown that ATM and DNA-PKcs signaling activates NF-kB through the p53-independent MEK/ERK/p90rsk/IKK signaling pathway in an antiapoptotic response to DNA damage (Panta et al, 2004). In addition, DNA-PKcs is required for the activation of the stress kinases SAPK/JNK (Fritz and Kaina, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This soon made possible the direct study of effects of single traversals through the cell nucleus (Miller et al 1999) or cytoplasm (Wu et al 1999) and evidence for the bystander effect (Zhou et al 2000). However, several other applications were soon introduced and technologies rapidly improved.…”
Section: Introductionmentioning
confidence: 99%